Adenosine Regulates the Proinflammatory Signaling Function of Thrombin in Endothelial Cells. Issue 9 (September 2014) - Hassanian, Seyed Mahdi; Dinarvand, Peyman; Rezaie, Alireza R.
<x xml:space="preserve">Abstract</x> The plasma level of the regulatory metabolite adenosine increases during the activation of coagulation and inflammation. Here we investigated the effect of adenosine on modulation of thrombin‐mediated proinflammatory responses in HUVECs. We found that adenosine inhibits the barrier‐disruptive effect of thrombin in HUVECs by a concentration‐dependent manner. Analysis of cell surface expression of adenosine receptors revealed that A2A and A2B are expressed at the highest level among the four receptor subtypes (A2B > A2A > A1 > A3) on HUVECs. The barrier‐protective effect of adenosine in response to thrombin was recapitulated by the A2A specific agonist, CGS 21680, and abrogated both by the siRNA knockdown of the A2A receptor and by the A2A‐specific antagonists, ZM‐241385 and SCH‐58261. The thrombin‐induced RhoA activation and its membrane translocation were both inhibited by adenosine in a cAMP‐dependent manner, providing a molecular mechanism through which adenosine exerts a barrier‐protective function. Adenosine also inhibited thrombin‐mediated activation of NF‐κB and decreased adhesion of monocytic THP‐1 cells to stimulated HUVECs via down‐regulation of expression of cell surface adhesion molecules, VCAM‐1, ICAM‐1, and E‐selectin. Moreover, adenosine inhibited thrombin‐induced elevated expression of proinflammatory cytokines, IL‐6 and HMGB‐1; and chemokines, MCP‐1, CXCL‐1, and CXCL‐3. Taken together, these results suggest that adenosine may inhibit thrombin‐mediated proinflammatory signaling responses, thereby protecting the endothelium from injury during activation of coagulation and inflammation. J. Cell. Physiol. 229: 1292–1300, 2014. © 2014 Wiley Periodicals, Inc.